Pengendalian Asam Lemak Bebas Crude Palm Oil Di PT. ZXY Dengan Seven Tools - Kiptiah, Mariatul; Ilmannafian, Adzani Ghani; Indra Darmawan, Muhammad; Latifah, Noor (Institut Teknologi Garut, 2025)
PT. ZXY is a company engaged in the processing of palm oil to produce Crude Palm Oil and Palm Kernel. A common problem in crude palm oil factories is a decline in the quality of crude palm oil caused by an increase in free fatty acid content. PT. ZXY has a free fatty acid standard of 3.50%, while the actual free fatty acid content can reach an average of 3.92%, making it necessary to control the quality of free fatty acids. The analysis was conducted using seven tools as aids to identify problems at PT. ZXY and can be used as a basis for improving the CPO production quality control system in the palm oil processing industry. The proposed improvements that can be made to enhance and control employee performance are the need to provide training on the proper implementation of SOPs with easy-to-understand information so that SOPs can be implemented properly.